The neonatal adverse event severity scale: current status, a stakeholders' assessment, and future perspectives - Allegaert, Karel; Salaets, Thomas; Wade, Kelly; Short, Mary A.; Ward, Robert; Singh, Kanwaljit; Turner, Mark A.; Davis, Jonathan M.; Lewis, Tamorah (Frontiers in Pediatrics, 2024)
To support informed decisions on drug registration and prescription, clinical trials need tools to assess the efficacy and safety signals related to a given therapeutic intervention. Standardized assessment facilitates reproducibility of results. Furthermore, it enables weighted comparison between different interventions, instrumental to facilitate shared decisions. When focused on adverse events in clinical trials, tools are needed to assess seriousness, causality and severity.As part of such a toolbox, the International Neonatal Consortium (INC) developed a first version of the neonatal adverse event severity scale (NAESS). This version underwent subsequent validation in retro-and prospective trials to assess its applicability and impact on the inter-observer variability. Regulators, sponsors and academic researchers also reported on the use of the NAESS in regulatory documents, trial protocols and study reports. In this paper, we aim to report on the trajectory, current status and impact of the NAESS score, on how stakeholders within INC assess its relevance, and on perspectives to further develop this tool.